Pemeriksaan Kadar Gula Darah dan Sosialisasi Bahaya Diabetes di SMA Muhammadiyah 1 Palangka Raya - Penia Penia; Noor Hujjatusnaini (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Diabetes mellitus (DM) is a metabolic disease characterized by elevated blood glucose levels. This condition includes several types, such as type 1 and type 2 diabetes. It occurs when the body is unable to produce enough insulin, experiences impaired insulin function, or faces a combination of both. As a result, glucose cannot be effectively absorbed by the body’s cells and accumulates in the bloodstream, leading to high blood sugar or hyperglycemia. If this condition persists, the buildup of glucose can cause various disorders in different organs. Without proper management, diabetes may lead to severe and life-threatening complications. Chronic hyperglycemia in diabetic patients is associated with long-term damage, dysfunction, and even failure of vital organs such as the eyes, kidneys, nerves, heart, and blood vessels. In this activity, percentage-based methods and demonstrations of blood glucose testing were used as educational tools for students. The results showed that students’ awareness of the dangers of elevated blood sugar levels remains low. Many of them are still unfamiliar with the importance of regular blood glucose monitoring and maintaining a healthy lifestyle to prevent diabetes. Therefore, continuous efforts are needed to provide education and outreach on the prevention and early management of diabetes mellitus.